Exploring the nutraceutical potential of soybean genotypes of Uttarakhand: implications for the mainstreaming of wild soybean - Oli, Pooja; Punetha, Shailaja; Wani, Zishan Ahmad; Arya, Om Prakash; Bhatt, I.D.; Singh, Dinesh Kumar (Frontiers in Sustainable Food Systems, 2024)
Climate change, coupled with the rising human population and increased demand for food, pose significant challenges for achieving the sustainable development goals (SDGs) of zero hunger, no poverty, and good health and well-being. These intertwined challenges demand urgent action to identify and promote un-popularized, underutilized, and unexplored climate-smart crops that can ensure food and nutritional security. The present study aimed to investigate the nutraceutical potential of Glycine soja, a wild ancestor of cultivated soybean that has been used traditionally as food and medicine in Indian Himalayas. Seed samples of wild and cultivated soybeans were collected from different locations in Uttarakhand, India, and screened for their phytochemical and biochemical contents using standard methods. The results of the study revealed that wild soybean contains a significant quantity of total phenols (27.44 ± 0.836 mg/g dw), flavonoids (3.319 ± 0.305 mg QE/g dw), and antioxidant activity (3.56 ± 1.090 mg AAE/g dw). Additionally, the species is a rich source of minerals such as zinc (4.68 ± 0.101 mg/100 g dw), vitamins, and amino acids such as histidine (0.95 ± 0.071 mg/100 g dw), isoleucine (1.74 ± 0.108 mg/100 g dw), leucine (2.94 ± 0.044 mg/100 g dw), lysine (2.13 ± 0.082 mg/100 g dw), methionine (0.53 ± 0.044 mg/100 g dw), threonine (0.67 ± 0.196 mg/100 g dw) etc. than the cultivated soybean. This study is the first to comprehensively compare phytochemicals, antioxidants, amino acids, vitamins, anthocyanins, and mineral content of wild and cultivated soybean seed quality traits. From the results of the present study, the inclusion of wild soybean in the cultivation system and daily diets might help to achieve livelihood, food and nutritional security.